COT-05 Experience of fertility preservation in 3 male cases and 1 female case with high-grade glioma. (28th November 2020) - Nakayama, Noriyuki; Yamada, Tetsuya; Yano, Hirohito; Kato, Yuki; Iwama, Toru
Abstract: High-grade glioma (HGG) has a low survival rate, and fertility preservation (FP) has rarely been discussed in the field of Japanese neurosurgery. We report on 4 reproductive patients, including 2 male patients who became biological fathers. Case 1 was a 23-year-old man with anaplastic oligodendroglioma (AO) of the right frontal lobe. Temozolomide maintenance therapy (TMZ-MT) was completed 42 courses after the initial surgery for economic reasons. 21 months later, a local recurrent lesion appeared, so TMZ-MT was restarted after removal this lesion. When he married at 32 years old, the couple wished a desire for childbearing. The TMZ-MT was stopped at 47 courses from the resumption and they aimed for spontaneous pregnancy. At 5 months after discontinuation of TMZ-MT, Gd-enhanced lesions increased again, so we changed the course to in vitro fertilization and resumed TMZ-MT. The couple had a biological baby at his 33 years and 10 months old. Case 2 was a 33-year-old married man with AO of the right parietal lobe. After partial removal, the FP information was explained and cryopreservation of sperm was performed. As of 23 months after the first operation, he became a biological father by in vitro fertilization. Case 3 was a 31-year-old married man with diffuse midline glioma (H3K27M mutant) in the cervical spinal cord. After partial removal, we provided FP information in the same manner, but the couple did not chose cryopreservation of sperm due to his mRS 5. Case 4 was a 24-year-old female with anaplastic astrocytoma of the brain stem. FP information was provided after stereotactic biopsy, but she chose to start radiochemotherapy without cryopreservation of eggs. Patients of reproductive age with HGG, especially oligodendroglial tumors who have a higher survival rate than astrocytic tumors, should be positively informed about FP before treatment begins.